Preclinical advance in nanoliposome-mediated photothermal therapy in liver cancer - Lixuan Tang; Xiao Yang; Liwen He; Chaogeng Zhu; Qingshan Chen (Lipids in Health and Disease)
Abstract Liver cancer is a highly lethal malignant tumor with a high incidence worldwide. Therefore, its treatment has long been a focus of medical research. Although traditional treatment methods such as surgery, radiotherapy, and chemotherapy have increased the survival rate of patients, their efficacy remains unsatisfactory owing to the nonspecific distribution of drugs, high toxicity, and drug resistance of tumor tissues. In recent years, the application of nanotechnology in the medical field has opened a new avenue for the treatment of liver cancer. Among these treatment methods, photothermal therapy (PTT) based on nanoliposomes has attracted wide attention owing to its unique targeting and high efficiency. This article reviews the latest preclinical research progress of nanoliposome-based PTT for liver cancer and its metastasis, discusses the preclinical challenges in this field, and proposes directions for improvement, with the aim of improving the effectiveness of liver cancer treatment.